Simulation Of Methyl Ethyl Ketone (MEK) Production In A Fixed Bed Reactor - Idris, Fatin Nur Liyana Mohd (Universiti Sains Malaysia, 2017)
SBA or sec-butanol alcohol is an intermediate product in order to produce methyl ethyl ketone (MEK) which is a solvent for cleaning agents and paint removers. SBA dehydrogenation process has been simulated, analysed and optimized with the Aspen Plus software version 8.8. SBA dehydrogenation model is developed and simulated in Aspen Plus. The fixed bed reactor which is multi-tubular reactor are modelled by plug flow reactor (PFR). The result obtained for the validation shows the simulation results almost follow the trend of the literature data on SBA conversion whereby the highest error is 18% and the least is 0.1%. Besides, sensitivity analysis is performed in model analysis tool in Aspen Plus to study the effect of reaction pressure, temperature and SBA feed flow rate towards the SBA conversion. The optimum values obtained in sensitivity analysis are 0.5 bar, 400°C and insignificantly changes for the SBA feed flow rate. In optimization section, the objective is to minimize the molar flow rate of SBA at the product stream in order to achieve highest optimized SBA conversion. The optimization is able to optimized the value of SBA molar flow rate at 13.4911 kmol/hr with highest optimized of SBA conversion which is 99.96% when the optimum temperature and pressure are 550°C and 0.5 bar respectively.